1504 BDNF and Oxidative Stress in Children with Acute Lymphoblastic Leukemia. (October 2012) - Alves, MMO; Carvalho, PRA; Marchesan, J; Michalowski, M; Daudt, LLE; Stertz, L; Ferrari, P; Gama, CS; Kapzinski, F
Abstract : Background: Acute lymphoblastic leukemia (ALL) is the most common malignancy in children, representing nearly one third of all pediatric cancers. Nowadays overall cure rates for children with ALL have reached 90% due to great improvements in diagnosis and treatment. Unfortunately, the increase in survival rates have been associated with an increase in treatment related toxicity. Survivors may experience late effects from treatment for this condition, such as learning disability and cognitive defects even with no cranial radiation. BDNF levels have been associated with cognitive deficits, among others conditions. Objectives: To evaluate the BDNF levels and oxidative stress in patients with acute lymphoblastic leukemia (ALL). Designand methods: We measured serum concentrations of brain derived neurothrophic factor (BDNF), serumthiobarbituric acid reactive substances (TBARS), serum protein carbonylation, serum IL-6 and IL-10 before and after 72 hours intratecal methotrexate (MTX). This study was performed on 8 children with ALL during the treatment with BFM protocol and in 40 controls. Results: BDNF levels were lower in ALL patients than in controls (p<0, 001). BDNF levels before and after intratecal MTX had not showed significant alterations. Serum protein carbonylation was lower after complete remission. Conclusion: These findings suggested that there is oxidative stress and decreased levels of serum BDNF in patients with acute lymphoblastic leukemia. The treatment may have a protective role in relation to oxidative stress and possible cognitive deficits.